Kajian Tentang Ruang Terbuka Hijau di Kecamatan Tenggarong Kabupaten Kutai Kartanegara - Slamet Riadi; Marlon Ivanhoe Aipassa; Yohanes Budi Sulistioadi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study discusses the green open space needed by every urban area in Tenggarong District. For this reason, this action aims to find out the condition of the area and the community's response to the existence of green open spaces in Tenggarong District. This research used a descriptive qualitative method. All the data used in the research came from observation, interviews and documentation which were then supported by other relevant data. The results show that green open space is a very vital need and must exist in urban areas with conditions that are progressing in development at any time. The condition is still below the minimum standard required for green open space, which is only 18.17%. For other results, it was stated that 46.7% agreed with green open spaces, 33.3% agreed, 20% disagreed. For this reason, green open space facilities and infrastructure must be considered by the government for the convenience of the community.